Analisis Butir Soal Ujian Akhir Semester Ganjil (UAS) Bahasa Jerman Kelas XII SMAN 1 Lawang - Hawanika, Cindy Audhila; Pujosusanto, Ari (LATERNE, 2021)
Question item analysis aims to determine the consistency of each item from the whole question. Based on the results of the analysis, some questions need to be revised, replaced, or stored as references. The formulation of the problem of this scientific article is how the validity, reliability, level of difficulty, distinguishing power, and effectiveness of the distractor of the multiple-choice questions of German Subject in the Final Examination (UAS) of the Odd Semester in class XII of SMAN 1 Lawang, in the Academic Year 2020/2021. This article aims to describe the validity, reliability, level of difficulty, distinguishing power, and the effectiveness of the distractor of the final exam questions for German Subject in class XII of SMAN 1 Lawang, in the Academic Year 2020/2021. It used a quantitative approach and the data were collected through documentation techniques. The data taken were the UAS question sheets with a total of 50 multiple choice questions, answer keys, answer sheets from 32 students, and a list of scores. Based on the results of the analysis, out of a total of 50 items, there are 24 valid questions and 26 invalid questions. The questions were unreliable with a result of -3.02. The test results for the difficulty level of the questions showed that there are 40 easy questions, 9 medium questions, and 1 difficult question. The results of the test for the distinguishing power of the questions were 25 questions with weak distinguishing power, 4 questions with sufficient distinguishing power, 1 question with good distinguishing power, 7 questions with excellent distinguishing power, and 13 questions with negative distinguishing power. The test of the effectiveness of the distractor showed that there are 1 question with good distractor effectiveness, 46 questions with moderate distractor effectiveness, 3 questions with poor effectiveness, and 0 questions with very poor effectiveness or no distractor.